Middle-age-onset cerebellar ataxia caused by a homozygous TWNK variant: a case report - Kodai Kume; Hiroyuki Morino; Ryosuke Miyamoto; Yukiko Matsuda; Ryosuke Ohsawa; Yuhei Kanaya; Yui Tada; Takashi Kurashige; Hideshi Kawakami (BMC, 2020)
Abstract Background The TWNK gene encodes the twinkle protein, which is a mitochondrial helicase for DNA replication. The dominant TWNK variants cause progressive external ophthalmoplegia with mitochondrial DNA deletions, autosomal dominant 3, while the recessive variants cause mitochondrial DNA depletion syndrome 7 and Perrault syndrome 5. Perrault syndrome is characterized by sensorineural hearing loss in both males and females and gonadal dysfunction in females. Patients with Perrault syndrome may present early-onset cerebellar ataxia, whereas middle-age-onset cerebellar ataxia caused by TWNK variants is rare. Case presentation A Japanese female born to consanguineous parents presented hearing loss at age 48, a staggering gait at age 53, and numbness in her distal extremities at age 57. Neurological examination revealed sensorineural hearing loss, cerebellar ataxia, decreased deep tendon reflexes, and sensory disturbance in the distal extremities. Laboratory tests showed no abnormal findings other than a moderate elevation of pyruvate concentration levels. Brain magnetic resonance imaging revealed mild cerebellar atrophy. Using exome sequencing, we identified a homozygous TWNK variant (NM_021830: c.1358G>A, p.R453Q). Conclusions TWNK variants could cause middle-age-onset cerebellar ataxia. Screening for TWNK variants should be considered in cases of cerebellar ataxia associated with deafness and/or peripheral neuropathy, even if the onset is not early.